SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/95685-ms
|View full text |Cite
|
Sign up to set email alerts
|

Waterflood Surveillance and Control: Incorporating Hall Plot and Slope Analysis

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractWaterflood automation at a field scale is a complex coupled problem. In our analysis, data from injecting and producing wells, as well as satellite differential interferograms (InSAR) are used as the inputs. Some information processing is carried out on-line automatically, and other needs personnel expertise. Dynamic adaptive control is performed in the mixed openloop-feedback mode. Our surveillance-control system is being implemented in Sections 32 and 33 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…) should be a straight line, and any deviation from the straight line indicates a change in formation properties and wellbore injectivity due to formation damage, fracture propagation or closure (see Figure 13). 181,264,265 Generally, a Hall plot is accepted as the most effective method for injection well performance analysis due to the steady-state condition of analysis and inexpensive data acquisition, as the only required information are the recorded daily wellhead pressures and injection rates. 266 Transient methods, such as PFO, are more expensive, as they require running gauges on wireline to depth and only provide the reservoir properties at one point in time, while the Hall plot identifies the injection effects occurring throughout an extended period of time.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…) should be a straight line, and any deviation from the straight line indicates a change in formation properties and wellbore injectivity due to formation damage, fracture propagation or closure (see Figure 13). 181,264,265 Generally, a Hall plot is accepted as the most effective method for injection well performance analysis due to the steady-state condition of analysis and inexpensive data acquisition, as the only required information are the recorded daily wellhead pressures and injection rates. 266 Transient methods, such as PFO, are more expensive, as they require running gauges on wireline to depth and only provide the reservoir properties at one point in time, while the Hall plot identifies the injection effects occurring throughout an extended period of time.…”
Section: 1mentioning
confidence: 99%
“…As discussed earlier, a “maximum sustainable injection pressure” is the differential pressure that can be used in a CO 2 injection process without creating new fractures or reactivating the pre-existing faults (usually 70–90% of fracture pressure). , During a CO 2 injection process, fracturing conditions might occur as a consequence of poroelastic or thermoelastic induced stresses. The formation damage caused by plugging of the pores throughout the processes such as drying-out or fines migration can also increase the BHPs to values above the fracturing pressure of formations.…”
Section: Maximum Sustainable Pressure In Co2 Injectionmentioning
confidence: 99%
“…Ojukwu and van den Hoek [3] state version for use in quantifying damage skin. Silin et al, [4] developed slope analysis to estimate and use the varying reservoir pressure term. Izgec and Kabir [5] completely reformulated the Hall plot in a way that accounts for variable radial distance of the injection bank and pressure at the water/oil interface.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the notable contributors include Buell et al (1990), who suggested the use of both bottomhole injection pressure and reservoir pressure instead of the wellhead pressure alone, as used in the conventional Hall plot. Evaluation of the reservoir pressure from a slope-analysis method was offered by Silin et al (2005aSilin et al ( , 2005b. Ideally, the Hall method is suitable for either early injection period or during the post-breakthrough period, because the notion of single-reservoir pressure is entertained.…”
Section: Introductionmentioning
confidence: 99%